Elderly suicides in Bolu province - Erdem Hösükler; Zehra Zerrin Erkol; Taşkın Özdeş; Tolga Turan; Buğra Kaan Yazgı (Northwestern Medical Journal)
Aim: The aim of this study was to analyze the characteristics of suicide cases in the elderly, identify risk factors and discuss preventive measures.